2022
DOI: 10.3390/ijerph192114553
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Perceived Community Support and Psychological Well-Being of Tourist Destinations Residents

Abstract: To explore the relationship between community support in tourist destinations and residents’ psychological well-being in the post-COVID-19 pandemic period, this study adopts the questionnaire survey method and draws the following conclusions by constructing a structural equation model: (1) perceived community support is very helpful for the psychological well-being of residents, (2) psychological resilience significantly mediates the relationship between perceived community support and residents’ psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…They observed that the increase of tourism activity generates resources that can be used for improving social conditions [42]. Moreover, the inherent interaction with tourism increases residents' level of knowledge [43], offering them new perspectives in life. Furthermore, one of the major consequences is that the local traditions are promoted [2].…”
Section: Impacts Of Tourism Developmentmentioning
confidence: 99%
“…They observed that the increase of tourism activity generates resources that can be used for improving social conditions [42]. Moreover, the inherent interaction with tourism increases residents' level of knowledge [43], offering them new perspectives in life. Furthermore, one of the major consequences is that the local traditions are promoted [2].…”
Section: Impacts Of Tourism Developmentmentioning
confidence: 99%
“…This has led to changes in economic, cultural, social, administrative measures of administrative department and the development strategies of tourist destinations [1][2][3]. On the other hand, studies have shown that COVID-19 has triggered a wide range of travel fears, not only for tourists, but also for residents in tourist destinations [4,5]. People's lifestyle has been forced to change, and research on the impact of the epidemic on the psychology and behavior of tourists and residents in tourist destinations has attracted more and more attention.…”
Section: Introductionmentioning
confidence: 99%